Penerapan model double loop problem solving berbasis eksperimen untuk meningkatkan keterampilan berpikir kritis pada materi panas dan perpindahannya pada peserta didik kelas v sekolah dasar - Rizky Ardhia Pramesti; Sri Marmoah; Tri Budiharto (Didaktika Dwija Indria, 2019)
Critical thinking skill is one of 21st century competency. Therefor, critical thinking skill is an important skill to face the desruption era. The purpose of this research is to enhancing the critical thinking skill trough double loop problem solving model based experiment. Utilizing a classrom action research which conducted in two cycles. Each cycles consist of four steps i.e planning, action, observation and reflection. The data was colected by using several technique such as observation, interview, documentation and critical thinking test. Also the data was validating by the expert because this research use validity content to validating the data. The interactive model was used to analyzing the data. The assessment of this research showed that both of student’s critical thinking skill and teacher’s performance increase continuesly. Based on the result, it can be concluded that trough double loopproblem solving model based experiment enhancing the student’s critical thinking skill of heat and transfer for V grade students.